Bis(3,5-dinitrobenzoato-kappa O-1)tetramethanolcobalt(II) - Sarkar, B.; Roy, A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The Co-II atom (site symmetry 1) in the title complex, [Co(C7H3N2O6)(2)(CH3OH)(4)], exists within an octahedral O-6 donor set defined by two O-monodentate 3,5-dinitrobenzoate anions and four methanol O atoms. An intramolecular O-m-H center dot center dot center dot Oc (m = methanol and c = carbonyl) hydrogen bond leads to the formation of an S(6) ring. In the crystal, centrosymmetrically related molecules associate via further O-m-H center dot center dot center dot Oc hydrogen bonds, leading to linear supramolecular chains propagating along the a-axis direction.